An adaptive solution for robust control based on integral high‐order sliding mode concept1. (17th January 2014) - Taleb, M.; Plestan, F.; Bououlid, B.
Summary A new high‐order sliding mode controller is proposed. The main features are gain adaptivity and the use of integral sliding mode concept. The gain adaptation allows a reduction of the chattering and gives a solution to control uncertain nonlinear systems whose the uncertainties/perturbations have unknown bounds. The concept of real high‐order sliding mode detector is introduced given that it plays a key role in the adaptation law of the gain. This new control approach is applied by simulation to an academic example to evaluate its efficiency. Copyright © 2014 John Wiley & Sons, Ltd.